Highly porous microlattices as ultrathin and efficient impact absorbers - Lai, Chang Quan (2018)
The deformation and impact energy absorption properties of ultrathin polymeric microlattices were investigated as a function of density, size and positional eccentricity of the trusses, which controlled the amount of bending in the microlattice deformations. We considered highly porous, 3-D microstructures with small lattice constants (≤135 μm), and studied their response to high strain rate (∼1000/s) tests, using high speed video capture, SEM imaging and quantitative modelling. The microlattices were found to have excellent impact absorption efficiencies that are 2 - 120 times better than carbon nanotube foams, polycarbonate and silicone rubber, despite being an order of magnitude slimmer than the thinnest commercial foams of similar densities. This high impact absorption efficiency is largely due to the sideways buckling of the microlattice trusses during the crushing stage, which prevented densification of the microlattices at small strains. Furthermore, we showed that varying the positional eccentricity of the trusses and the number of unit cells in the microlattices can modulate their stiffness, strength and energy absorption over an appreciable range, comparable to that obtained through modifications in relative density. Because the microlattices were mostly under stress equilibrium during the impact process, the insights derived from the present study are expected to be valid for quasistatic and low strain rate loadings as well.